The Effect of Supportive Education on Foot Care Knowledge in Type 2 Diabetes Mellitus - Saiful Gunardi (UIMA Press, 2024)
Background: Diabetes Mellitus is a disease that hides before real symptoms appear, such as easy hunger, thirst and frequent urination. Other symptoms are skin disorders such as itching, tingling, numbness due to neuropathy, physical weakness, and wounds on the feet that heal slowly, so foot care is needed for DM patients who have wounds on their feet. Objectives: To determine the effect of supportive education on knowledge of diabetic foot care in type 2 diabetes mellitus patients. Methods: This study used a one group pre-test – post-test design using the Wilcoxon test, with a population and sample of 30 respondents, the instrument was a questionnaire on knowledge of foot care in DM patients. Results: Based on the results of analysis using the Wilcoxon Signed Ranks Test method, it was obtained that the P value was 0.000 <0.05, so it can be concluded that there is an influence of supportive education on knowledge of diabetic foot care in type 2 DM patients. Conclusion: With the influence of supportive education on knowledge of diabetic foot care in DM patients, in providing nursing care you can apply this supportive education in the care of DM patients.